Enjeux, difficultés et modalités de l’expression sur le travail : point de vue de la clinique médicale du travail - Philippe Davezies (Perspectives Interdisciplinaires sur le Travail et la Santé)
Regardless of the job sector or hierarchical position, work intensification forces workers to make hard choices between the different goals they are expected to meet. Due to a lack of discussion, people have to manage by themselves. The consequences are a rising tide of interpersonal conflicts and occupational stress associated with a deterioration in overall performance. This situation requires that time and places be set aside for work disputes, in keeping with French law. Nevertheless, there is a serious difficulty in actualizing this law: the worker’s tacit knowledge of his work is much richer than his conscious ability to verbalize and describe the work activity. Self-governed, employee-reserved times and places for working out the stakes at issue are necessary before discussing with the administration if we are to arrive at favourable results for occupational health and overall company performance.